Immunomodulatory Roles of Polysaccharide Capsules in the Intestine - Hsieh, Samantha A.; Allen, Paul M. (Frontiers in Immunology, 2020)
The interplay between the immune system and the microbiota in the human intestine dictates states of health versus disease. Polysaccharide capsules are critical elements of bacteria that protect bacteria against environmental and host factors, including the host immune system. This review summarizes the mechanisms by which polysaccharide capsules from commensal and pathogenic bacteria in the gut microbiota modulate the innate and adaptive immune systems in the intestine. A deeper understanding of the roles of polysaccharide capsules in microbiota-immune interactions will provide a basis to harness their therapeutic potential to advance human health.